The association between accelerometer-determined physical activity and nutritional status among USM staff - Radzi, Najibah Nabilah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
The aim for this study was to determine the association between accelerometerdetermined physical activity and nutritional status among Universiti Sains Malaysia (USM) staff. A total of 41 Malay (25 males and 16 females) employees participated in this study. Body weight, height, waist and hip circumferences, and body composition were measured for each respondent. All respondents were asked to wear an accelerometer for seven days. Based on body mass index, majority (41.5%) of the respondents were overweight, while 17.1% were obese, 39% were normal and only 2.4% were underweight. According to waist circumference measurement, 39% of respondents were identified to have abdominal obesity. Majority of the respondents (56.1%) were classified to have low active physical activity and 26.8% of them were sedentary. Meanwhile, 14.6% were somewhat active and only 2.4% were having active physical activity. There were no significant association between physical activity level and BMI (r=0.23, p=0.153), waist circumference (rs=0.25, p=0.119), waist-hip ratio (rs=0.02, p=0.906), total body fat (r=0.15, p=0.360) and visceral fat rating (r=0.22, p=0.168). In conclusion, there is no significant association between accelerometerdetermined physical activity level and nutritional status among USM staff.